2021
DOI: 10.1259/bjr.20201013
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging in the evaluation of pathologic nipple discharge: indications and imaging findings

Abstract: Pathologic nipple discharge (PND) is typically unilateral, spontaneous, involves a single duct, and is serous or bloody in appearance. In patients with PND, breast MRI can be helpful as an additional diagnostic tool when conventional imaging with mammogram and ultrasound are negative. MRI is able to detect the etiology of nipple discharge in 56–61% of cases when initial imaging with mammogram and ultrasound are negative. Advantages to using MRI in evaluation of PND include good visualization of the retroareola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 93 publications
0
7
0
Order By: Relevance
“…More than 90 % of Paget's disease cases are associated with an underlying breast malignancy. Therefore, even when traditional mammography and ultrasound do not reveal abnormalities, additional imaging studies such as breast MRI should be considered for further evaluation, especially in patients with PDN [ 3 ]. Lim et al [ 8 ] underscored the significance of MRI in Paget's disease and reported its importance in assessing the nipple-areolar complex and detecting potential underlying breast malignancies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More than 90 % of Paget's disease cases are associated with an underlying breast malignancy. Therefore, even when traditional mammography and ultrasound do not reveal abnormalities, additional imaging studies such as breast MRI should be considered for further evaluation, especially in patients with PDN [ 3 ]. Lim et al [ 8 ] underscored the significance of MRI in Paget's disease and reported its importance in assessing the nipple-areolar complex and detecting potential underlying breast malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…This condition was first documented by a British surgeon, Sir James Paget, in 1874. PDN typically affects the skin around the nipple in women and is associated with an underlying breast carcinoma, accounting for approximately 1 %–3 % of breast malignancies [ [1] , [2] , [3] , [4] ]. Despite its relative rarity, PDN poses significant diagnostic and therapeutic challenges due to its clinical similarity to benign dermatological conditions and its frequent association with in situ or invasive carcinoma (observed in 90 %–100 % of cases) [ 1 , 2 , [5] , [6] , [7] , [8] , [9] ].…”
Section: Introductionmentioning
confidence: 99%
“…The detection of breast cancer is based on angiogenesis, and after one to two minutes of administration of gadolinium, there is prompt uptake and release due to the increased permeability of tumor blood vessels [4]. Studies show MRI has a 93-100% sensitivity for detecting invasive breast cancer but is not generally used unless suspicion for malignancy remains high after MMG and US are inconclusive [1][2][3][4]. Ductography is an invasive procedure that can cause discomfort and pain and can only be used when discharge is present as the duct that is draining is cannulated and filled with dye to allow for evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…Nipple discharge presents in approximately 3-10% of women and is classified as either physiological or pathological. Physiologic discharge can be green, white, or yellow and presents bilaterally and non-spontaneously [ 1 ]. Benign papilloma is the most common etiology of pathologic nipple discharge [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation